Marijuana use among adult liver transplant candidates and recipients. Issue 7 (19th April 2021) - Likhitsup, Alisa; Saeed, Naba; Winder, Gerald Scott; Hassan, Ammar; Sonnenday, Christopher J; Fontana, Robert J
Abstract: Background: Data regarding marijuana (MJ) use among liver transplant (LT) candidates are limited. We set out to determine the incidence and pre and postLT outcomes of adult LT candidates with a self‐reported history of MJ use. Methods: Baseline clinical characteristics, waitlist, and post‐LT outcomes of adult LT candidates from January 2010 to March 2017 were compared. Results: Among 2690 LT candidates, 630(23%) and 298(11%) reported a history of MJ use and use within the past 12 months, respectively. Although the proportion of MJ users increased over time( β = .76, p = .03), the proportion listed and transplanted did not change. Listing for LT increased with male (OR 1.24, 95% CI 11.01–1.52), MELD score (OR 1.08, 95% CI 1.01–1.15), HCC (OR 1.83, 95% CI 1.39–2.41) but decreased among MJ users (OR 0.67, 95% CI 0.50–0.91, p = .01). The median time to listing was longer among MJ users compared to non‐users (115 vs. 87 days, p < .0005). PostLT survival was similar in 83 MJ users and 306 non‐users. Conclusion: The proportion of MJ users among LT candidates is increasing. MJ users have a greater burden of psychosocial issues which may contribute to longer evaluations and lower rate of LT listing. Post‐LT survival was not impacted by self‐reported MJ use history.